Demand Flexibility in Supply Chain Planning - Geunes, Joseph (SpringerBriefs in Optimization, 2012)
This work encapsulates the essential developments in this field into a single resource, as well as to set an agenda for further development in the field. This brief focuses on the demand flexibility in supply chains with fragmented results distributed throughout the literature. These results have strong implications for managing real-world complex operations planning problems. This book exploits dimensions of demand flexibility in supply chains and characterizes the best fit between demand properties and operations capabilities and constraints. The origins and seminal works are traced in integrated demand and operations planning and an in-depth documentation is provided for the current state of the art. Systems with inherent costs and constraints that must respond to some set of demands at a minimum cost are examined.  Crucial unanswered questions are explored and the high-value research directions  are highlighted for both practice and for the development of new and interesting optimization models and algorithms.